2012
DOI: 10.1177/1555343412461254
|View full text |Cite
|
Sign up to set email alerts
|

Complex Perceptual-Cognitive Expertise in a Simulated Task Environment

Abstract: In popular models of expertise and decision making in complex environments, such as the recognitionprimed decision (RPD) model and take-the-first (TTF) heuristic, expert and skilled decision makers are described as generating few response options and typically choose the best option first. To explain these behaviors, proponents of TTF have suggested that a negative relationship exists between the number of options generated and decision quality. In the current article, we use a prediction and situational optio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

20
211
6
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 75 publications
(239 citation statements)
references
References 31 publications
(104 reference statements)
20
211
6
2
Order By: Relevance
“…Furthermore, Ward et al [9] examined how soccer players anticipate other players' movements in a complex environment. For this experiment, the authors selected 41 soccer players of whom 21 were classified as skilled and 20 as less-skilled.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, Ward et al [9] examined how soccer players anticipate other players' movements in a complex environment. For this experiment, the authors selected 41 soccer players of whom 21 were classified as skilled and 20 as less-skilled.…”
Section: Discussionmentioning
confidence: 99%
“…We found that these analyses were performed with the aim of comparing players regarding their competitive level [1,2,[8][9][10][11][13][14][15]. In the study of Ward and Williams [8], videotaped scenes were used to assess (besides anticipation), memory and situational probabilities (i.e.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Findings have demonstrated that elite players generally accumulate significantly more hours of sport-specific engagement compared to less skilled players (Roca et al, 2012;. Furthermore, researchers using video-based assessments have demonstrated perceptual-cognitive skills such as decision-making, situational probability assessment, and pattern recognition, differentiate skilled and lesser skilled athletes (Ward et al, 2013;Ward & Williams, 2003;Williams et al, 2006). However, researchers have not explored the potential relationship between these sport-specific variables and grit.…”
mentioning
confidence: 99%
“…Participants' performance was specified by the position they finished in the national competition, with results indicating grittier spellers performed better than less gritty spellers. Duckworth and From a sporting perspective, researchers have demonstrated an expertise effect for perceptual-cognitive skills (Ward, Ericsson, & Williams, 2013;Ward & Williams, 2003;Williams, Hodges, North, & Barton, 2006), and sport-specific engagement Roca et al, 2012;. Retrospective recall techniques have been used to identify the time invested by skilled and less skilled players in sport-specific activities such as competition, training, and play.…”
mentioning
confidence: 99%